Behavior of North American mammals - Elbroch, Mark (Peterson reference guide series., 2011)
Provides detailed information on the behavior of more than 70 species of mammals, along with photographs and drawings, that includes daily and seasonal activities, food and foraging, home range and habitat, communication, courtship and mating, development and dispersal of young, interactions within a species, and interactions with other species.